Factors Behind Cessation of Illegal Logging by Local Communities for Valuable Timber-producing Endemic Species, Hopea celebica (Jurnal Penelitian Kehutanan Wallacea, 2024)
Hopea celebica is a species of Dipterocarpaceae that produces strong and durable wood. This species is endemic to Sulawesi Island, where its spread is restricted to specific habitat types in the southern part of the island. The high quality of the wood has exposed this species to high levels of illegal logging and is endangered. However, in the last two decades, the threat of logging to this tree species has ceased to occur. Through field surveys and interviewing of respondents in 6 small FGDs, this study aims to determine the factors behind the cessation of illegal logging activities. We found that this species has good regeneration ability and identified 3 leading causes of stopping illegal logging of H. celebica: restricting its habitat to the Bantimurung Bulusaraung National Park, the change in cultural interest from building houses on stilts to concrete houses, and the shift in the lifestyle of young generation who are no longer interested in working as woodcutters. Thus, the cessation of illegal logging of H. celebica is not due to the correct public perception of the importance of conserving H. celebica to increase its population so that it can be used sustainably in the future. The Bantimurung Bulusaraung National Park still needs to make people aware of the importance of H. celebica conservation.
Keywords: karst ecosystem; regeneration; conservation; sustainable